AN ANALYSIS OF DIFFERENCE IN FEMALES AND MALES ATTITUDE TOWARDS ECO-FRIENDLY PRACTICES AT HOME (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Eco-friendly behavior, sometimes referred to as green behavior or eco-behavior, is the idea that people,  groups, and communities should make decisions and take activities to reduce their environmental effect and advance  ecological sustainability. Ecological behavior is essential for maintaining biodiversity, protecting ecosystems, and  conserving natural resources. The current study focuses on the environmentally conscious actions that Bhopal city’s  men and women take at home. Objective: The objective of the study was to examine the attitude of men and women  towards eco friendly habits at home. Methodology: The present research is quantitative, in nature. The study was  conducted in the Bhopal city. Convenience sampling was used for the collection of the data. Respondents were asked  closed-ended questions on 5-point Likert scale related to their demographic profile and their attitude towards eco friendly practices at home. 270 responses from162 male and 108 were female respondents aged more than 18 years was  collected. Descriptive statistics was adopted to get the results of present research. Results: In order of importance male  showcased importance for saving water (84%), switch the light off when leaving a room (76.5%), use of energy efficient  light bulbs (76.5%) and turn AC off in unoccupied rooms (75.3%) are the top four eco-friendly practices. For female  switching the light off when leaving a room (90.7%), saving water (83.3%), turning AC off in unoccupied rooms (81.5%)  and turning heat off in unoccupied rooms (79.6%) were the top four eco-friendly practices followed at their homes.  Conclusion: Saving water, switching the light off when leaving a room, using of energy efficient light bulbs and turning  AC off in unoccupied rooms were the top four eco-friendly practices which are mostly practiced by males at their homes.  For female switching the light off when leaving a room, saving water, Turning AC off in unoccupied rooms and Turning  heat off in unoccupied rooms were the top four eco-friendly practices.
Keywords: Eco-friendly Practices; Males Eco-friendly Behavior; Females Eco-friendly Behavior; Home